On Some Solvable Classes of Nonlinear Nonisospectral Difference Equations - Mokhonko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We investigate different measure transformations of the mapping-multiplication type in the cases where the corresponding chains of differential equations can be efficiently found and integrated.